Optimal design of a DC MHD pump by simulated annealing method - Bouali Khadidja; Kadid Fatima Zohra; Abdessemed Rachid (Serbian Journal of Electrical Engineering, 2014)
In this paper a design methodology of a magnetohydrodynamic pump is proposed. The methodology is based on direct interpretation of the design problem as an optimization problem. The simulated annealing method is used for an optimal design of a DC MHD pump. The optimization procedure uses an objective function which can be the minimum of the mass. The constraints are both of geometrics and electromagnetic in type. The obtained results are reported.